ANALISIS MINAT BERWIRAUSAHA: PENGARUH LOCUS OF CONTROL INTERNAL DAN EXTERNAL MELALUI SELF-EFFICACY (Studi Kasus Mahasiswa Universitas Fajar) - Sri Adrianti Muin; Abdul Majid Bakri; ST. Rukaiyah; Windi Azzahra (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to predict and develop the structural relationship between internal and external locus of control and its impact on entrepreneurship intention through self-efficacy. This research was studied using quantitative methods to find out and analyze the direct and indirect relationship between locus of control internal and locus control external on Fajar University students' entrepreneurship intention through self-efficacy. This research used a sample of 113 students at Fajar University with a purposive sampling technique and a confidence level of 95%. The research instrument was measured using a Likert scale with a value interval of 1 to 5. Next, the data was analyzed using SmartPLS 3, both reflectively and formatively. The research results obtained were 1) a significant positive impact of the locus of control internal variable on self-efficacy, 2) a significant positive impact of the locus of control external variable on self-efficacy, 3) a significant positive effect of locus of control internal on entrepreneurship intention, 4) effect significant positive impact of locus of control external on entrepreneurship intention, 5) a significant positive impact of self-efficacy on entrepreneurship intention, 6) a significant positive impact of locus of control internal through self-efficacy on entrepreneurship intention, 7) a significant positive impact of locus of control external through self-efficacy in entrepreneurship intention.